Kompensasi Finansial dan Stres Kerja Terhadap Kepuasan Kerja Mitra Driver PT. Go-Jek Indonesia (Go-Ride) - Runtulalo, Axel R.; Areros, William A.; Sambul, Sofia A. P. (Productivity, 2020)
This study aims to determine the Effect of Compensation and Job Stress on Job Satisfaction of the Go-Ride Driver of PT. GO-JEK Indonesia in Manado. This approach uses a quantitative approach, with a sample of 100 respondents. This sampling technique uses Purposive Sampling technique. Data collection techniques in this research is to use a questionnaire distribution study. The analysis technique used in this study is using SPSS 21.00. the results of the study showed that compensation had a significant and positive effect on job satisfaction. This means that the higher Compensation will lead to higher Job Satisfaction, Job Stress has a significant and negative effect on Job Satisfaction. This means that the higher the Job Stress, the lower the Job Satisfaction. Simultaneously, Compensation and Job Stress were able to explain the effect on Job Satisfaction of 57.7%, the rest were influenced by other variables outside this study. Increasing Compensation and Minimizing Job Stress will result in Job Satisfaction of the Go-Ride Driver PT. GO-JEK Indonesia in Manado.